SAPI PERAH (SATU PION PENJELAJAH SEJARAH) SEBAGAI MEDIA PEMBELAJARAN IPS SEJARAH HINDU BUDHA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SDN SAMIRONO YOGYAKARTA - Rahmani Hakim, Latifa Dinar; Pangestu, Dimas Aldi; Andini, Ghina (Pelita - Jurnal Penelitian Mahasiswa UNY, 2015)
This research aims to (1) to find out the application of Sapi Perah learning media to the grade IV SDN Samirono, (2) to find out the process of learning history of Hinduism and Buddhism through the use of Sapi Perah learning media, and (3) to reveal the improvement of the understanding and learning ability of grade IV students of Samirono Elementary School. The method used is classroom action research involving two cycles. In the first cycle, the students were given a description of the history of Hinduism and Buddhism. Then, they were given a pre test on the material that has been taught and tried to apply the Sapi Perah learning media. However, the results were not satisfying because they were not enthusiastic in learning. The second cycle was conducted by applying the learning media of Sapi Perah again. In the second cycle optimal results were obtained. The students’ learning outcomes of the history of Hinduism and Buddhism improved. The results of this research are (1) the application of a learning media Sapi Perah can improve the students’ understanding of the history of Hinduism and Buddhism and (2) the learning process in the classroom becomes more interesting because of the use of the media of Sapi Perah.